Neonatal acute megakaryoblastic leukemia mimicking congenital neuroblastoma. Issue 3 (2nd December 2014) - Kawasaki, Yukako; Makimoto, Masami; Nomura, Keiko; Hoshino, Akihiro; Hamashima, Takeru; Hiwatari, Mitsuteru; Nakazawa, Atsuko; Takita, Junko; Yoshida, Taketoshi; Kanegane, Hirokazu
Key Clinical Message We describe a neonate with abdominal distension, massive hepatomegaly, and high serum neuron‐specific enolase level suggestive of congenital neuroblastoma. The patient died of pulmonary hemorrhage after therapy. Autopsy revealed that the tumor cells in the liver indicated acute megakaryocytic leukemia with the RBM15‐MKL1 fusion gene.